Efficacy and safety of long-term administration of dienogest for deep infiltrative endometriosis - Volkov V.G; N.E. Malykh (LCC «Medicine-Inform», 2019)
V.G. Volkov1, N.E. Malykh2 1Tula State University, Tula, Russian Federation 2Tula Multidisciplinary Medical Center «Consultant Farm», Tula, Russian Federation Deep infiltrative endometriosis is a type of endometriosis characterized by 5-mm penetration of pathological tissue in the affected structure. Treatment approaches to endometriosis still remain elusive. Chronic nature of this disease requires long-term therapeutic strategies up to menopause thus taking years and even decades. To follow the principle of "no more than one surgical procedure in a woman with endometriosis" or to avoid the surgery, one should select highly effective but also safe medications. Progestins, in particular, dienogest, are first-line choice for endometriosis. The paper reviews published data on dienogest use in women with deep infiltrative endometriosis and analyses its mechanism of action. Advantages of dienogest as compared with other progestins are discussed. Special attention is paid to its effects on pain and dyspareunia. Potential treatment complications and their prevention are addressed. Need for long-term administration is ju stified. Current data demonstrate that 2 mg daily of dienogest (Visanne) prescribed postoperatively after the surgery for deep infiltrative endometriosis are effective and safe. Keywords: genital endometriosis, pain, dyspareunia, progestin, dienogest, Visanne. For citation: Volkov V.G., Malykh N.E. Efficacy and safety of long-term administration of dienogest for deep infiltrative endometriosis. Russian Journal of Woman and Child Health. 2019;2(3):226-230.